Pengembangan Media Pembelajaran Interaktif Plant Flash Pada Materi Bagian-bagian Tumbuhan Untuk Siswa Kelas IV Sekolah Dasar - Argi Dias Damara; Ilham Arvan Junaidi; Puji Ayu Rachmawati (Universitas Negeri Padang, 2021)
This development research aims to: Knowing the procedures, validity, practicality of the development of interactive learning media Plant Flash for Fourth Grade Elementary School Students. The method used in this research is ADDIE (Research and Development) model. This research was conducted at SD Negeri 74 Palembang. The method used in data collection is a questionnaire. The trial was conducted 2 times consisting of: 1. One to One,2. Small Group. The implementation stage is a large-scale trial conducted on 30 students. Based on the results of the study, it was shown that the assessment by material 1 experts got a score of 90%, material 2 experts got a score of 78%, media experts were 96%. Meanwhile, student assessments in the one to one trial were obtained in the